The Role of Ethnoscience-Integrated E-Modules in Science Learning: A Systematic Literature Review - Naya Mahdiyya Sari; Nurmala Mustofa; Nasywa Dwi Kamila; Rizka Isnaeni (Indonesian Journal of STEM Education, 2026)
The development of digital technology in education encourages the use of innovative teaching materials such as E-Modules that support independent, interactive, and flexible learning. On the other hand, science learning requires a contextual approach that connects scientific concepts with real-life situations, one of which is through ethnoscience. However, studies that systematically synthesize the roles and impacts of ethnoscience-integrated E-Modules in science learning are still limited; therefore, comprehensive research in this area is needed. This study aims to systematically examine the role of ethnoscience-integrated E-Modules in science learning. The method used is a Systematic Literature Review (SLR) by analyzing 14 relevant articles published between 2016 and 2025, obtained from Google Scholar using Publish or Perish. The article selection process followed the PRISMA flow, while data analysis was conducted using content analysis techniques. The results show that ethnoscience-integrated E-Modules are able to improve the quality of learning through contextual, interactive, and culture-based content, as well as contribute to enhancing students’ learning independence, motivation, scientific literacy, and conceptual understanding. However, their implementation still faces challenges such as limited technological facilities and teachers’ readiness, so support in the form of training and adequate facilities is needed to optimize their use. Therefore, ethnoscience-integrated E-Modules have great potential as an innovative approach in future science learning.